Impact of Economic Growth on Unemployment in South Africa: A Time-Series Data Analysis - Nomusa Yolada Nkomo; Eyitayo Francis Adanlawo (Research Synergy Foundation, 2024)
Debates over the relationship between economic growth and unemployment are crucial for monetary policymaking. Unemployment is a major challenge in developing countries. The country's high unemployment rate reflects the poor use of labor resources. Hence, unemployment is a huge economic issue that has a negative influence on individuals and society at large. This nexus has also been associated with drug addiction and criminal activity in numerous countries, including South Africa. Given the importance of this topic, the macroeconomic literature contains several theories and models that examine the connection between economic growth and unemployment. For proper formulation and implementation of effective monetary policy, the relationship between these macroeconomic variables is critical. Using quarterly time series data for South Africa from 2002 to 2020, this study examines the impact of economic growth on unemployment. DOLS assumptions were used to investigate the impact of the two variables; the end results show that there is a negative relationship between economic growth and unemployment, which is consistent with previous studies that follow the hypothesis that unemployment is negatively impacted by economic growth. These findings will assist policymakers in developing strategies to regulate unemployment and promote long-term growth within countries.